PRODUCTIVITY ESTIMATES FROM ALPINE TUNDRA IN BRITISH COLUMBIA - BRINK, V. C.; LUCKHURST, A.; MORRISON, D. (Canadian Journal of Plant Science, 1972)
Estimates of net primary productivity and combined nitrogen content are given for exclosures on three alpine sites in British Columbia. The estimates are useful for determining carrying capacity of alpine ranges for domestic and native ungulates, for comparative studies in biological zonation, and for environmental sensitivity decisions.